2020
DOI: 10.1108/er-07-2019-0292
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of employee commitment in the relationship between quality of work life and the intention to stay

Abstract: PurposeThe aim of this study is to investigate the relationship between quality of work life (QWL), employee commitment and the intention to stay of nurses in private hospitals in Malaysia.Design/methodology/approachA cross-sectional survey design was used in this study. Primary data were collected through self-administered questionnaires with nurses as the respondents from four private hospitals in the states of Selangor and Kuala Lumpur, Malaysia. Out of 300 questionnaires distributed, 202 valid responses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 55 publications
3
58
0
5
Order By: Relevance
“…A good understanding of which physical, emotional and behavioral symptoms of health problems do employees face during the COVID-19 epidemic could improve better health, well-being, productivity and satisfaction among employees during the COVID-19 and also after the COVID-19. According to Lee (2021), Agus and Selvaraj (2020), Srivastava and Agarwal (2020), Zhang et al (2020), Shareena and Mahammad (2020) and Hayes and Curran (2020), there is more need for suitable human resource management during the COVID-19 epidemic and suitable working environment for employees during the COVID-19 epidemic and also after the COVID-19 epidemic. Moreover, Stein (2020), Gavidia ( 2020 The study findings show that physical, emotional and behavioral symptoms of health problems among employees during the COVID-19 epidemic are more strongly expressed as before the COVID-19 epidemic, and also the study findings show that there are significant differences regarding physical, emotional, and behavioral symptoms of health problems among employees who worked from home and those who worked at the workplace during the COVID-19 epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…A good understanding of which physical, emotional and behavioral symptoms of health problems do employees face during the COVID-19 epidemic could improve better health, well-being, productivity and satisfaction among employees during the COVID-19 and also after the COVID-19. According to Lee (2021), Agus and Selvaraj (2020), Srivastava and Agarwal (2020), Zhang et al (2020), Shareena and Mahammad (2020) and Hayes and Curran (2020), there is more need for suitable human resource management during the COVID-19 epidemic and suitable working environment for employees during the COVID-19 epidemic and also after the COVID-19 epidemic. Moreover, Stein (2020), Gavidia ( 2020 The study findings show that physical, emotional and behavioral symptoms of health problems among employees during the COVID-19 epidemic are more strongly expressed as before the COVID-19 epidemic, and also the study findings show that there are significant differences regarding physical, emotional, and behavioral symptoms of health problems among employees who worked from home and those who worked at the workplace during the COVID-19 epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…High quality work life is achieved through attention to the philosophy of employee relations and is the use of efforts to use quality work life, which are regular efforts by an organisation that gives employees greater opportunities to influence their work and work together and organise overall effectiveness. (Agus & Selvaraj, 2020) With the help of QWL processes, the organisation can respond to the needs of employees in creating a mechanism to allow them to fully participate in the decisions that design their lives in the workplace. (Allam & Shaik, 2020) Employees sometimes use QWL to mean that they are the only source of livelihood and financial needs of the organisation.…”
Section: Qualitymentioning
confidence: 99%
“…This is despite the fact that the development of Barmi models in our society to identify the QWL and its dimensions has received less attention since these non-indigenous models are not necessarily based on the work culture of Iranian organisations and also often based on Quantitative methods have been measured, for example, domestic research mentioned in the field of backgrounds, so it can be said that most domestic research has only identified components of quality of work life based on non-native patterns. Also, the problem with quantitative measurements is that they are too mechanical and inflexible, neglecting to examine the impact indicators considered by the participants in the research sample, and only measuring the indicators that are assumed by the researchers (Agus & Selvaraj, 2020;. This not only causes a kind of incomplete identification of the components but may also have a biased effect on participants' responses (Agus & Selvaraj, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the findings indicate that employee commitment partially mediates the relationship between quality of work life and the intention to stay. Researchers concluded that nurses are satisfied with their quality of work-life, the stronger will the nurses' commitment be in the organization and finally their intention to stay [6]. As per Dorgham (2012), it is significant in displaying how the organization has to work hard in order to keep its employees committed to the organization.…”
Section: Introductionmentioning
confidence: 99%